PHILOLOGIST-METHODOLOGICAL DEVELOPMENT OF LEXICAL COMPETENCE BY ACTIVATING PHRASEOLOGICAL UNITS IN STUDENT SPEECH: PHILOLOGIST-METHODOLOGICAL DEVELOPMENT OF LEXICAL COMPETENCE BY ACTIVATING PHRASEOLOGICAL UNITS IN STUDENT SPEECH - Jalgasbaeva, Gulnaz (Журнал иностранных языков и лингвистики, 2025)
Lexical competence is a fundamental component of linguistic proficiency, particularly in the context of second or foreign language acquisition. Among the many ways to enhance this competence, the integration of phraseological units—such as idioms, collocations, and set expressions—proves both linguistically enriching and culturally informative. Philologists and educators are increasingly focusing on how these units can be methodologically employed to develop students’ expressive abilities and comprehension in academic and everyday speech.